Utility of MRI for Characterizing Articular Cartilage Pathology in Dogs with Medial Coronoid Process Disease - Franklin, Samuel P.; Burke, Emily E.; Holmes, Shannon P. (Frontiers in Veterinary Science, 2017)
Objective: To determine whether assessment of morphological MRI sequences or delayed gadolinium enhanced MRI of cartilage (dGEMRIC) would have strong correlations with arthroscopic assessment of cartilage pathology in dogs with naturally occurring medial compartment pathology of the elbow. Methods: Dogs tentatively diagnosed with medial coronoid disease had evaluation of their affected elbows using radiography, morphological MRI sequences, and dGEMRIC MRI evaluation prior to arthroscopy. Elbow radiographs were graded 0-6 for severity of changes. Cartilage of the medial coronoid process (MCP) and humeral trochlea were scored on a 0-3 scale using anatomical MRI sequences. The T1 relaxation times for the MCP and trochlea were quantified using dGEMRIC. Cartilage pathology was graded arthroscopically using a modified Outerbridge score (MOS) by a surgeon blinded to MRI assessment. Correlations between radiography and MOS, and between MRI and MOS, were quantified. Results: Twenty-six elbows in 14 dogs were evaluated. There were statistically significant (p<0.05) moderate correlations between radiographic scores and MOS for the MCP (r=0.71) and humeral trochlea (0.57). There was a statistically significant moderate correlation between morphological MRI scoring and MOS for the humeral trochlea (r=0.54; p<0.05) but not for the MCP (p>0.05). There was a weak but significant correlation between the dGEMRIC value and MOS of the MCP (r = 0.41; p<0.05) but no correlation between the dGEMRIC values and MOS for the humeral trochlea (p>0.05). Clinical relevance: Statistically significant correlations to MOS were identified for both radiography and MRI but neither diagnostic modality provided sufficiently strong correlations to serve as a substitute for arthroscopic evaluation of the articular cartilage.